SISTEM INFORMASI PELAYANAN MASYARAKAT BERBASIS ANDROID PADA KANTOR DESA KALIBA MAMASE - Ritnawati, Ritnawati; Suppa, Rinto; Muhallim, Muhlis (Universitas Ahmad Dahlan, 2020)
The problem in this thesis research is how to design an Android-Based Community Service Information System at the KalibaMamase Village office. Information Systems for Community Services are based on the system using Black Box Testing and the accuracy of the information system is based on user testing. The research objective is to design and build a Village-level Community Service Information System in order to improve the quality of services for village staff and the use of services for local villagers. The benefit obtained from this research is to make a new innovation for each village to be able to facilitate serving residents or residents in the application for letters. This research uses the life cycle model of the Waterfall system development and the design of an Android-based population service information system. Data collection methods in this study use the method of observation, interviews, and data analysis. The conclusion of the research is that the Community Service Information System can facilitate the process of correspondence services in the Village apparatus as well as the use of services for the community in managing population and obtaining information at the Village Office. In the Android-Based Community Service Information System at the Kaliba Mamase Village Office